Influence of Ion Vacancy Migration on Short‐Circuit Current of Perovskite Solar Cells. Issue 18 (26th June 2022) - Lin, Zedong
Abstract : For perovskite solar cells (PSCs), the effect of ion vacancy motion on the short‐circuit current ( J sc ) in the reverse and forward J – V scans is investigated. To reveal its mechanism, all the components of current (carrier current, ionic current, displacement current) at the short‐circuit working point are calculated and the action of mobile ion vacancy on them is explored. By adjusting the parameters determining the ion vacancy mobility μ I, the effect of parameter μ I on J sc is discussed. The finding provides a great supplement for the theory of short‐circuit current. Abstract : For perovskite solar cells, the influence of ion vacancy migration on the short‐circuit current is deeply revealed. The ionic current itself shows a negligible contribution to the total short‐circuit current. The mobile ions influence the carrier current by the modulation of the internal electric field and, through it, affect the total short‐circuit current.